Efektivitas Penggunaan Media Audio Visual Untuk Meningkatkan Kemampuan Menghafal Surat-Surat Pendek (Al-Insyiroh) Pendek Pada Kelompok B - Aidil Izzah; Farlina Hardianti (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2025)
Audio visual media with the help of learning videos is expected to be able to attract students' attention and concentration on the material so that the message or information is quickly conveyed This research aims to improve the ability to memorize short letters (Al insyiroh). The approach uses classroom actions with the Kemmis model. The research involved 11 Tkit Tahfiz Qur'an Human Intellectual students. The results of the research show that the use of audio-visual media is effective in increasing the ability to memorize Surah Al Insyiroh with a percentage. In cycle I the student's ability was 80% and in cycle II it increased to 100%. In cycle I the average score obtained was 85%. -an average score of 70 and increased in cycle II to 100% classical completeness obtained with an average score of 80. Along with these learning results, student involvement, interest, students' motivation, creativity and understanding. Teachers' abilities in operating media, creating learning content, creativity and managing learning also increase. However, it is also necessary to pay attention to concentration, focus, learning environment and student satisfaction to support the optimization of learning.